Waste polishing solution acid-excited geopolymer recycled concrete and preparation method thereof

By using waste polishing liquid as an acid exciter, combined with waste red brick fine powder and high brick concrete construction waste recycled aggregate, geological polymer mortar is prepared, which solves the problems of low utilization rate of brick concrete construction waste and large load in cement production environment, and improves the mechanical properties and durability of geological polymer recycled concrete, and promotes the comprehensive utilization and green development of waste materials.

CN119912208AActive Publication Date: 2025-05-02BEIJING UNIV OF CIVIL ENG & ARCHITECTURE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510119179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the prior art, brick-concrete construction waste has poor reactivity, high water absorption and low strength, resulting in low utilization. At the same time, cement causes severe environmental load and energy consumption in the production process, and lacks alternative solutions for green resourced gelling materials.

Method used

Use waste polishing liquid as an acid exciter, combine waste red brick fine powder and high brick concrete construction waste regenerated aggregate to prepare geological polymer mortar, and obtain geological polymer regenerated concrete with excellent mechanical properties and water absorption through high temperature curing.

Benefits of technology

The mechanical properties and durability of geological polymer recycled concrete have been improved, and the preparation of geological polymer concrete has been completely replaced by cement, which has reduced carbon emissions and promoted the comprehensive utilization of waste materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912208A_ABST
    Figure CN119912208A_ABST
Patent Text Reader

Abstract

The invention discloses waste polishing solution acid-excited geopolymer recycled concrete and a preparation method thereof, the geopolymer recycled concrete comprises 12-20wt% of geopolymer, 72-80wt% of aggregate and 8-10wt% of water, and the geopolymer comprises 60-68wt% of waste red brick micro powder, 25-32wt% of waste polishing solution and 7-12wt% of deionized water. The preparation method comprises the following steps: preparing a geopolymer, and dispersing the geopolymer in water to form a flowing geopolymer; drying the coarse aggregate, the fine aggregate and the high brick-concrete construction waste recycled aggregate of each grade of particle size; and mixing the flowing geopolymer with all aggregates to obtain the waste polishing solution acid-excited geopolymer recycled concrete. The geopolymer prepared by the invention has excellent performance, and can completely replace cement to prepare geopolymer concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering materials and environmental protection, and specifically relates to a waste polishing liquid acid-activated geopolymer regenerated concrete and a preparation method thereof. Background Art

[0002] With the continuous acceleration of the implementation of projects such as urbanization, old city renovation, and urban village renovation, the contradiction between construction, resources and the environment has become increasingly acute. Urbanization has significantly increased the amount of construction waste generated.

[0003] Construction waste is usually divided into concrete construction waste with low brick-concrete content and brick-concrete construction waste with high brick-concrete content. After processing the two types of construction waste, recycled concrete aggregate and recycled brick-concrete aggregate can be obtained respectively. Recycled concrete aggregate comes from waste concrete, and recycled brick-concrete aggregate comes from waste bricks and tiles. Concrete and bricks and tiles (i.e. red bricks, red brick fragments, tiles, etc.) are two different solid waste materials. In concrete construction waste with low brick-concrete content, the content of concrete is high, and the content of bricks and tiles is very low. The chemical composition is mainly CaO and CaCO3, which are alkaline substances, with a small number of internal pores and small pores; in brick-concrete construction waste with high brick-concrete content, the content of bricks and tiles is high, and the content of concrete is very low. The chemical composition is mainly SiO2 and Al2O3, which are acidic substances, with a large number of internal pores and large pores.

[0004] With the continuous increase in the transformation of urban and rural towns, many village and town buildings have been demolished one after another, especially for brick-concrete structures. The brick-concrete construction waste generated after demolition is very large, and appropriate methods should be adopted to treat it as solid waste and transform it into a usable renewable resource. At present, the disposal method of brick-concrete construction waste is to use it as recycled aggregate, roadbed filling material and mineral admixture after treatment, but the reactivity of brick-concrete construction waste is poor, the water absorption rate is high and the strength is low, which leads to the low utilization rate of brick-concrete construction waste; however, brick-concrete construction waste is rich in alumina and silica, has certain volcanic ash activity, and has great potential in preparing cementitious materials as a precursor material.

[0005] As we all know, cement is the most widely used cementitious material in the construction industry. However, cement will cause serious environmental load and huge energy consumption during the production process. The use of green resource cementitious materials to replace cement will become an urgent problem to be solved. Geopolymer concrete and cement concrete are two different types of concrete. Geopolymer concrete is a mixture of geopolymer mortar and aggregate, and cement concrete is a mixture of cement and aggregate. At present, the research on how to completely replace cement concrete with geopolymer concrete has attracted widespread attention from academia and industry. Geopolymer mortar is the core of geopolymer concrete, which is used to bond aggregate particles. The performance of geopolymer mortar directly affects the overall quality and comprehensive performance of geopolymer concrete.

[0006] At present, there are many studies on alkali-activated cementitious materials, and their applications are becoming more mature. However, while alkali-activated cementitious materials are developing rapidly, they have also encountered some problems, such as rapid setting, alkali-aggregate reaction, unstable strength, large shrinkage, specimen cracking, etc. Moreover, alkali-activated cementitious materials require the use of some professional equipment in the preparation process, which consumes a lot of energy and causes waste of resources. Therefore, it is necessary to explore new activation methods.

[0007] Phosphate-based geopolymer is an inorganic aluminosilicate polymer with a three-dimensional network structure composed of [AlO4], [SiO4] and [PO4] tetrahedrons. Compared with alkali-activated geopolymers, phosphate-based geopolymers have the advantages of high strength, good high-temperature thermal stability, low dielectric constant and dielectric loss. Waste phosphate-based polishing liquid is an industrial waste liquid generated in the aluminum processing process. Its main component is phosphoric acid, and it also contains a large amount of metal ions such as aluminum and iron. If it is directly discharged without treatment, it will cause serious pollution to the environment and waste resources. Therefore, the development of a waste polishing liquid acid-activated geopolymer recycled concrete and its preparation method is an extremely urgent need in the field of road engineering materials.

[0008] The invention patent with application publication number CN116768537A discloses an acid-activated multi-waste ecological stone for gabions and a preparation method thereof, which is prepared from waste silicon-aluminum source, acid activator, waste aggregate and water; the content of each substance in the waste silicon-aluminum source is 25-40% blast furnace slag powder, 25-40% fly ash, 5-10% manganese slag powder, 10-20% waste red brick powder, 5-10% waste concrete powder, 5-10% bagasse ash, and 5-10% rice husk ash; the acid activator is an expired phosphoric acid-based polishing liquid; the content of each substance in the waste aggregate is 12-20% waste tailings sand, 12-20% waste red brick sand, and 60-76% recycled concrete coarse aggregate. This technical solution utilizes various types of solid waste materials, and the performance of the stone used in the gabion also meets the requirements, but there are still some problems: (1) Due to the use of various types of waste, the uncertainty of the final stone performance is high; (2) The mortar is not cured, and the performance of the mortar needs to be improved, which affects the performance of the final stone. Summary of the invention

[0009] In order to solve the problems existing in the prior art, the present invention provides a waste polishing liquid acid-activated geopolymer regeneration concrete, wherein the mass percentage of each substance in the geopolymer regeneration concrete is 12-20wt% of geopolymer, 72-80wt% of aggregate, 8-10wt% of water, and the sum of the contents of each substance is 100wt%; the mass percentage of each substance in the geopolymer is 60-68wt% of waste red brick powder, 25-32wt% of waste polishing liquid, and 7-12wt% of deionized water, and the sum of the contents of each substance is 100wt%.

[0010] Preferably, the waste red brick powder is recycled powder obtained by processing construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 100%; the particle size distribution of the waste red brick powder is between 1-15μm, and the mass percentage of each particle size of the waste red brick powder is 20-40wt% for particle size 8-15μm and 60-80wt% for particle size 1-8μm.

[0011] In any of the above schemes, it is preferred that in the waste red brick powder with a particle size of 8-15μm, the mass percentage of each chemical substance in the waste red brick powder is 45-50wt% SiO2, 25-30wt% Al2O3, 8-15wt% Fe2O3, 2-5wt% CaO, 1-3wt% MgO, 1-3wt% Na2O, 1-3wt% K2O, 1-2wt% TiO2, 1-2wt% P2O5, 0.5-1wt% MnO, and the sum of the contents of each chemical substance is 100wt%.

[0012] In any of the above schemes, it is preferred that in the waste red brick powder with a particle size of 1-8 μm, the mass percentage of each chemical substance in the waste red brick powder is 60-65wt% SiO2, 15-20wt% Al2O3, 5-8wt% Fe2O3, 2-5wt% CaO, 1-3wt% MgO, 1-3wt% Na2O, 1-3wt% K2O, 1-2wt% TiO2, 1-2wt% P2O5, 0.5-1wt% MnO, and the sum of the contents of each chemical substance is 100wt%.

[0013] In any of the above schemes, it is preferred that the mass percentage of each chemical substance in the waste polishing liquid is 76-80wt% of phosphoric acid, 3-5wt% of sulfuric acid, 1-2wt% of nitric acid, 3-8wt% of Al ions, 2-5wt% of Fe ions, 1-2wt% of Ca ions, 1-2wt% of Mg ions, and 8-11wt% of water, and the sum of the contents of each chemical substance is 100wt%.

[0014] In any of the above schemes, it is preferred that the mass percentage of each substance in the aggregate is 24-30wt% of coarse aggregate, 32-38wt% of fine aggregate, and 35-40wt% of high-brick-concrete construction waste recycled aggregate, and the sum of the contents of each substance is 100wt%.

[0015] In any of the above schemes, it is preferred that the coarse aggregate includes three particle sizes, and the mass percentage of each particle size in the coarse aggregate is: particle size 16-19 mm accounts for 25-35wt%, particle size 9.5-16 mm accounts for 32-42wt%, particle size 4.75-9.5 mm accounts for 30-40wt%, and the sum of the content of coarse aggregate in each particle size is 100wt%; the coarse aggregate includes any one or more of limestone, basalt, and granite.

[0016] In any of the above schemes, it is preferred that the fine aggregate includes seven particle sizes, and the mass percentage of each particle size in the fine aggregate is: particle size 2.36-4.75mm accounts for 22-28wt%, particle size 1.18-2.36mm accounts for 22-28wt%, particle size 0.6-1.18mm accounts for 20-25wt%, particle size 0.3-0.6mm accounts for 7-10wt%, particle size 0.15-0.3mm accounts for 5-8wt%, particle size 0.075-0.15mm accounts for 5-8wt%, particle size 0-0.075mm accounts for 5-8wt%, and the sum of the content of fine aggregate in each particle size is 100wt%; the fine aggregate includes any one or more of limestone, basalt, and granite.

[0017] In any of the above schemes, it is preferred that the high-brick-concrete construction waste recycled aggregate is a recycled aggregate obtained after processing of construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 60-70%; the high-brick-concrete construction waste recycled aggregate includes three particle sizes, and the mass percentage of each particle size in the high-brick-concrete construction waste recycled aggregate is, particle size 16-19mm accounts for 25-30wt%, particle size 9.5-16mm accounts for 38-45wt%, particle size 4.75-9.5mm accounts for 30-35wt%, and the sum of the contents of each particle size high-brick-concrete construction waste recycled aggregate is 100wt%.

[0018] The present invention also provides a method for preparing waste polishing liquid acid-activated geopolymer regenerated concrete, which is used to prepare any of the waste polishing liquid acid-activated geopolymer regenerated concrete described above, and comprises the following steps in order:

[0019] Step 1: Weigh all raw materials according to the designed material ratio;

[0020] Step 2: Prepare geopolymer according to the designed material ratio and process parameters;

[0021] Step 3: Put the geopolymer and water into a mixing pot and mix them to make the geopolymer completely dispersed to form a fluid geopolymer;

[0022] Step 4: Put the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the recycled aggregates of high-quality brick-concrete construction waste of various particle sizes into an oven for drying;

[0023] Step 5: After the drying process is completed, the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the high-brick-concrete construction waste recycled aggregates of various particle sizes are put into the mixing pot and mixed with the fluid geopolymer to obtain the waste polishing liquid acid-activated geopolymer recycled concrete.

[0024] Preferably, in step 2, the method for preparing the geopolymer comprises the following steps in order:

[0025] Step (1): crushing, grinding and screening construction waste generated by demolishing brick-concrete buildings with a brick-concrete content of 100% to obtain waste red brick powder;

[0026] Step (2): weighing waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm according to the designed material ratio, and putting them into an oven for drying respectively, the drying temperature is 80-100° C., and the drying time is 2-3 h; after the drying treatment is completed, taking out the waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm from the oven respectively, and cooling them naturally to room temperature;

[0027] Step (3): According to the designed chemical content ratio, the chemical substances in the waste red brick micropowder with a particle size of 8-15 μm and a particle size of 1-8 μm are tested respectively to ensure that the content of each chemical substance in the waste red brick micropowder of each particle size meets the design requirements;

[0028] Step (4): according to the designed material ratio, the waste polishing liquid is added into deionized water for dilution to a phosphoric acid concentration of 8-12 mol / L, sealed and naturally cooled to room temperature to obtain an acid activator;

[0029] Step (5): putting waste red brick powder with a particle size of 8-15 μm and part of the acid activator into a mixing pot for mixing to form a first group of mortar, wherein the mass of the part of the acid activator is 30-50% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 80-120 r / min, and the mixing time is 100-150 s;

[0030] Step (6): putting the waste red brick powder with a particle size of 1-8 μm and the remaining acid activator into another mixing pot for mixing to form a second group of mortar, wherein the mass of the remaining acid activator is 50-70% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 80-120 r / min, and the mixing time is 100-150 s;

[0031] Step (7): putting the first group of mortar and the second group of mortar into the same mixing pot for mixing, the mixing temperature is room temperature, the mixing speed is 150-200r / min, and the mixing time is 200-250s to obtain geopolymer mortar, which is in a fluid state;

[0032] Step (8): filling the geopolymer mortar into the molding mold, and using a scraper to scrape the upper surface of the geopolymer mortar in the molding mold flat; placing the molding mold filled with the geopolymer mortar on an electric vibration table, starting the electric vibration table, and starting vibration molding. During the vibration molding process, if a depression occurs, the geopolymer mortar is added to the depressed part;

[0033] Step (9): After the vibration molding is completed, the molding mold and the molded part inside are placed in a curing box for high-temperature curing, the curing temperature is 60-80° C., and the curing time is 24-36 hours; after the high-temperature curing is completed, demoulding is performed, and then the molded part is subjected to standard curing under sealed conditions, the curing temperature is room temperature, and the curing time is 28 days, so that the geopolymer is obtained, and the geopolymer is in a solid state.

[0034] In any of the above schemes, preferably, in step three, the mixing temperature of the geopolymer and water is room temperature, the mixing speed is 50-80 r / min, and the mixing time is 90-120 s.

[0035] In any of the above schemes, it is preferred that in step 4, the drying temperature of coarse aggregate of each particle size, fine aggregate of each particle size, and high brick-concrete construction waste recycled aggregate of each particle size is 80-100°C and the drying time is 2-3h.

[0036] In any of the above schemes, it is preferred that in step five, the mixing temperature of coarse aggregate of various particle sizes, fine aggregate of various particle sizes, high brick-concrete construction waste recycled aggregate of various particle sizes, and fluid geopolymer is room temperature, the mixing speed is 150-200r / min, and the mixing time is 120-150s.

[0037] In the present invention, the coarse aggregate includes three particle sizes, namely, particle size 16-19mm, particle size 9.5-16mm, and particle size 4.75-9.5mm, that is, 16mm≤particle size<19mm, 9.5mm≤particle size<16mm, and 4.75mm≤particle size<9.5mm. The fine aggregate includes seven particle sizes, namely 2.36-4.75mm, 1.18-2.36mm, 0.6-1.18mm, 0.3-0.6mm, 0.15-0.3mm, 0.075-0.15mm and 0-0.075mm, that is, 2.36mm≤particle size<4.75mm, 1.18mm≤particle size<2.36mm, 0.6mm≤particle size<1.18mm, 0.3mm≤particle size<0.6mm, 0.15mm≤particle size<0.3mm, 0.075mm≤particle size<0.15mm and 0mm≤particle size<0.075mm. High brick-concrete construction waste recycled aggregate includes three particle sizes, namely 16-19mm, 9.5-16mm, and 4.75-9.5mm, that is, 16mm≤particle size<19mm, 9.5mm≤particle size<16mm, and 4.75mm≤particle size<9.5mm. The particle size distribution of waste red brick micropowder is between 1-15μm, including two particle sizes, namely 8-15μm and 1-8μm, that is, 8μm≤particle size≤15μm, and 1μm≤particle size<8μm. For each particle size, the material passes through the upper and lower sieve holes in sequence to obtain a particle size between the upper and lower sieve holes, for example: the particle size is 1.18-2.36mm (1.18mm≤particle size<2.36mm), that is, the material passes through the 2.36mm sieve hole and the 1.18mm sieve hole in sequence to obtain a particle size between 1.18-2.36mm.

[0038] The technical principle of the present invention: H in the acid activator + Reacts with Al2O3 in the precursor, breaks the Al-O bond, and reacts with SiO4 4- 、AlO4 2- and PO4 3-The waste polishing liquid of the present invention has the advantage of being an acid activator in that it can react with waste red brick micropowder to generate phosphorus-oxygen tetrahedrons, which can be connected with the layered structure of the waste polishing liquid to form a more stable three-dimensional network structure, and can also balance the Al 3+ The positive charge makes the entire structure electrically neutral, and the Al contained in the waste polishing liquid 3+ and other metal ions can react with PO4 in the waste polishing liquid 3- , H + and [H9Si2O8] + Plasma condensation forms more gel phases, so the mechanical properties of the gelled material stimulated by the waste polishing liquid of the present invention are more excellent.

[0039] The present invention has been proved through a large number of tests that the waste polishing liquid is diluted in deionized water, and the concentration of phosphoric acid reaches 8-12 mol / L, which is the optimal concentration range. When the acid concentration is too high, the heat release is large in the initial stage of the reaction, causing the slurry to coagulate prematurely, hindering the depolymerization of aluminosilicate and resulting in incomplete reaction, so that a large amount of unreacted precursors remain in the microstructure. When the acid concentration is too low, there is too much free water in the solution, and the excess water does not participate in the polymerization reaction and gradually dissipates during the curing process, resulting in more pores in the geopolymer structure. At the same time, too low an acid concentration will also cause Al 3+ Priority and PO3 4- An amorphous structure mainly composed of P—O—Al is formed, which will also make its structure loose and porous, reducing the strength of the geopolymer.

[0040] The invention has been proved through a large number of tests that after the geopolymer mortar is vibrated and formed, it is placed in a curing box for high-temperature curing, the curing temperature is 60-80°C, and the curing time is 24-36h, and the curing temperature and curing time are in the optimal range.

[0041] In the geopolymerization reaction, the depolymerization reaction and the polymerization reaction proceed simultaneously. If the reaction temperature is low, it is conducive to a more complete depolymerization reaction, more silicon and aluminum are dissolved, and it is conducive to the formation of more gel phases, but it is not conducive to the removal of water and hydroxyl groups in the geopolymer during the polycondensation reaction stage, affecting its compressive strength. On the contrary, if the reaction temperature is high, although it is conducive to the removal of water and hydroxyl groups in the geopolymer, it shortens the depolymerization process and affects the dissolution of silicon and aluminum in the precursor; in addition, too high a reaction temperature will cause the water in the molded part to evaporate too quickly, resulting in inconsistent shrinkage rates between the surface and the inside of the molded part, causing microcracks in the molded part, thereby affecting its compressive strength.

[0042] When the curing time is short, the reaction between the precursor and the acid activator is incomplete, and some hydroxyl groups in the molded parts are difficult to remove; appropriately extending the curing time can effectively optimize the product structure and improve the performance of the geopolymer. If the curing time is too long, the strength of the geopolymer will not increase significantly or even not increase, wasting time and cost.

[0043] The waste polishing liquid acid-activated geopolymer regeneration concrete and the preparation method thereof of the present invention involve many parameters, including formula parameters and process parameters, and the parameters need to work synergistically to achieve the expected technical effect of the present invention, especially the content of each chemical substance in the waste red brick micropowder of two particle sizes, and when preparing geopolymers, the waste red brick micropowder of two particle sizes needs to react with the acid activator to form mortar respectively, and then the two groups of mortars are mixed to prepare geopolymer mortar. In the whole process of preparing geopolymer regeneration concrete, the selection and addition amount of each substance, the addition order of each substance, the process parameters of each step, etc. are also very important, and each formula parameter and process parameter need to work synergistically.

[0044] In the present invention, the waste red brick powder and high brick-concrete construction waste recycled aggregate used are all recycled materials obtained after processing of construction waste generated by the demolition of brick-concrete buildings. These two materials are different from solid waste materials such as industrial waste slag (such as steel slag, slag, zinc slag, manganese slag, etc.), coal liquefaction residue (such as direct coal liquefaction residue, indirect coal liquefaction residue, etc.), concrete construction waste (low brick-concrete content), etc. The ways of obtaining these solid waste materials, the realization principles, the physical and chemical properties, etc. are all different.

[0045] In the present invention, the mixing pot, electric vibration table, oven, curing box, crushing equipment, grinding equipment, screening equipment, etc. used are all traditional equipment in the field. There are no special requirements for the equipment model and it can be selected according to actual usage. It only needs to ensure that key parameters such as mixing speed, mixing time, drying temperature, drying time, curing temperature, curing time, etc. meet the requirements of the present invention.

[0046] The waste polishing liquid acid-activated geopolymer regenerated concrete and the preparation method thereof of the present invention have the following beneficial effects:

[0047] (1) The present invention uses waste red brick powder as a precursor and waste polishing liquid as an acid activator to prepare geopolymer mortar, and then obtains geopolymer through high-temperature curing. The geopolymer has excellent mechanical properties and water absorption rate.

[0048] (2) The geopolymer of the present invention can completely replace cement to prepare geopolymer concrete, and the geopolymer concrete has excellent mechanical properties and durability.

[0049] (3) The present invention also comprehensively utilizes waste materials such as waste red brick powder, waste polishing liquid, and high-brick-concrete construction waste recycled aggregate, thereby reducing carbon emissions and promoting the utilization of renewable resources and the green development of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 A flowchart of a preferred embodiment of the waste polishing liquid acid-activated geopolymer regenerated concrete and a preparation method thereof according to the present invention;

[0051] Figure 2 for Figure 1 Actual photos of waste red brick powder used in the examples shown;

[0052] Figure 3 for Figure 1 Actual photos of the waste polishing liquid used in the illustrated embodiment;

[0053] Figure 4 for Figure 1 The actual photos of the aggregates used in the illustrated embodiments, wherein: (a) is coarse aggregate, (b) is fine aggregate, and (c) is recycled aggregate from high-quality brick-concrete construction waste;

[0054] Figure 5 for Figure 1 The actual photographs of the geopolymer prepared in the illustrated embodiment, wherein: (a) is the state before high temperature curing, and (b) is the state after high temperature curing;

[0055] Figure 6 for Figure 1 Microscopic morphology photos of geopolymers prepared in the examples shown;

[0056] Figure 7 for Figure 1 XRD test spectrum of the geopolymer prepared in the embodiment shown;

[0057] Figure 8 for Figure 1 Actual photograph of the geopolymer recycled concrete prepared in the illustrated example. DETAILED DESCRIPTION

[0058] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0059] Embodiment 1:

[0060] According to a preferred embodiment of the waste polishing liquid acid-activated geopolymer regenerated concrete of the present invention, the mass percentage of each substance in the geopolymer regenerated concrete is 16wt% of geopolymer, 76wt% of aggregate, and 8wt% of water; the mass percentage of each substance in the geopolymer is 64wt% of waste red brick powder, 27wt% of waste polishing liquid, and 9wt% of deionized water.

[0061] The waste red brick powder is recycled powder obtained by processing construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 100%; the particle size distribution of the waste red brick powder is between 1-15μm, and the mass percentage of each particle size of the waste red brick powder is: 30wt% for particle size 8-15μm, and 70wt% for particle size 1-8μm.

[0062] In the waste red brick powder with a particle size of 8-15 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 48wt%, Al2O3 accounts for 28wt%, Fe2O3 accounts for 11wt%, CaO accounts for 3wt%, MgO accounts for 2wt%, Na2O accounts for 2wt%, K2O accounts for 2wt%, TiO2 accounts for 1.5wt%, P2O5 accounts for 1.5wt%, and MnO accounts for 1wt%.

[0063] In the waste red brick powder with a particle size of 1-8 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 63wt%, Al2O3 accounts for 18wt%, Fe2O3 accounts for 6wt%, CaO accounts for 3wt%, MgO accounts for 2wt%, Na2O accounts for 2wt%, K2O accounts for 2wt%, TiO2 accounts for 1.5wt%, P2O5 accounts for 1.5wt%, and MnO accounts for 1wt%.

[0064] The mass percentages of the chemical substances in the waste polishing liquid are as follows: 77wt% phosphoric acid, 4wt% sulfuric acid, 1wt% nitric acid, 4wt% Al ions, 3wt% Fe ions, 1wt% Ca ions, 1wt% Mg ions, and 9wt% water.

[0065] The mass percentage of each substance in the aggregate is: 27wt% of coarse aggregate, 35wt% of fine aggregate, and 38wt% of recycled aggregate from high-quality brick-concrete construction waste.

[0066] The coarse aggregate includes three particle sizes, and the mass percentage of each particle size in the coarse aggregate is: particle size 16-19mm accounts for 30wt%, particle size 9.5-16mm accounts for 35wt%, and particle size 4.75-9.5mm accounts for 35wt%. The coarse aggregate is limestone.

[0067] The fine aggregate includes seven particle sizes, and the mass percentage of each particle size in the fine aggregate is: particle size 2.36-4.75mm accounts for 25wt%, particle size 1.18-2.36mm accounts for 25wt%, particle size 0.6-1.18mm accounts for 22wt%, particle size 0.3-0.6mm accounts for 8wt%, particle size 0.15-0.3mm accounts for 6wt%, particle size 0.075-0.15mm accounts for 7wt%, and particle size 0-0.075mm accounts for 7wt%. The fine aggregate is limestone.

[0068] The high-grade brick-concrete construction waste recycled aggregate is a recycled aggregate obtained after processing of construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 65%; the high-grade brick-concrete construction waste recycled aggregate includes three levels of particle size, and the mass percentage of each particle size of the high-grade brick-concrete construction waste recycled aggregate is: particle size 16-19mm accounts for 28wt%, particle size 9.5-16mm accounts for 40wt%, and particle size 4.75-9.5mm accounts for 32wt%.

[0069] like Figure 1 As shown, this embodiment also provides a method for preparing waste polishing liquid acid-activated geopolymer regenerated concrete, which is used to prepare the above waste polishing liquid acid-activated geopolymer regenerated concrete, and includes the following steps in order:

[0070] Step 1: Weigh all raw materials according to the designed material ratio;

[0071] Step 2: Prepare geopolymer according to the designed material ratio and process parameters;

[0072] Step 3: Put the geopolymer and water into a mixing pot and mix them to make the geopolymer completely dispersed to form a fluid geopolymer;

[0073] Step 4: Put the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the recycled aggregates of high-quality brick-concrete construction waste of various particle sizes into an oven for drying;

[0074] Step 5: After the drying process is completed, the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the high-brick-concrete construction waste recycled aggregates of various particle sizes are put into the mixing pot and mixed with the fluid geopolymer to obtain the waste polishing liquid acid-activated geopolymer recycled concrete.

[0075] In step 2, the method for preparing the geopolymer comprises the following steps in order:

[0076] Step (1): crushing, grinding and screening construction waste generated by demolishing brick-concrete buildings with a brick-concrete content of 100% to obtain waste red brick powder;

[0077] Step (2): according to the designed material ratio, waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm are weighed and placed in an oven for drying, respectively, at a drying temperature of 90° C. and a drying time of 2.5 h; after the drying treatment is completed, the waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm are taken out of the oven respectively, and naturally cooled to room temperature;

[0078] Step (3): According to the designed chemical content ratio, the chemical substances in the waste red brick micropowder with a particle size of 8-15 μm and a particle size of 1-8 μm are tested respectively to ensure that the content of each chemical substance in the waste red brick micropowder of each particle size meets the design requirements;

[0079] Step (4): according to the designed material ratio, the waste polishing liquid is added into deionized water for dilution to a phosphoric acid concentration of 10 mol / L, and the mixture is sealed and naturally cooled to room temperature to obtain an acid activator;

[0080] Step (5): putting waste red brick powder with a particle size of 8-15 μm and part of the acid activator into a mixing pot for mixing to form a first group of mortar, wherein the mass of the part of the acid activator is 40% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 100 r / min, and the mixing time is 125 s;

[0081] Step (6): putting the waste red brick powder with a particle size of 1-8 μm and the remaining acid activator into another mixing pot for mixing to form a second group of mortar, wherein the mass of the remaining acid activator is 60% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 100 r / min, and the mixing time is 125 s;

[0082] Step (7): putting the first group of mortar and the second group of mortar into the same mixing pot for mixing, the mixing temperature is room temperature, the mixing speed is 175r / min, the mixing time is 225s, and the geopolymer mortar is obtained, and the geopolymer mortar is in a fluid state;

[0083] Step (8): filling the geopolymer mortar into the molding mold, and using a scraper to scrape the upper surface of the geopolymer mortar in the molding mold flat; placing the molding mold filled with the geopolymer mortar on an electric vibration table, starting the electric vibration table, and starting vibration molding. During the vibration molding process, if a depression occurs, the geopolymer mortar is added to the depressed part;

[0084] Step (9): After the vibration molding is completed, the molding mold and the molded part inside are placed in a curing box for high-temperature curing, the curing temperature is 70° C., and the curing time is 30 hours; after the high-temperature curing is completed, demoulding is performed, and then the molded part is subjected to standard curing under sealed conditions, the curing temperature is room temperature, and the curing time is 28 days, so that the geopolymer is obtained, and the geopolymer is in a solid state.

[0085] In step 3, the mixing temperature of geopolymer and water is room temperature, the mixing speed is 65r / min, and the mixing time is 105s.

[0086] In step 4, the drying temperature of coarse aggregate of each particle size, fine aggregate of each particle size, and high-brick-concrete construction waste recycled aggregate of each particle size is 90° C. and the drying time is 2.5 h.

[0087] In step five, the mixing temperature of coarse aggregate of various particle sizes, fine aggregate of various particle sizes, high-brick-concrete construction waste recycled aggregate of various particle sizes, and fluid geopolymer is room temperature, the mixing speed is 175r / min, and the mixing time is 135s.

[0088] In this embodiment, the waste red brick powder used is as follows: Figure 2 As shown; the waste polishing liquid used is as follows Figure 3 The aggregates used are as shown in Figure 4 As shown, (a) is coarse aggregate, (b) is fine aggregate, and (c) is recycled aggregate from high-quality brick-concrete construction waste; the prepared geopolymer is as follows Figure 5 As shown in FIG. 1 , wherein: (a) is the state before high temperature curing, and (b) is the state after high temperature curing; the microscopic morphology of the prepared geopolymer is as shown in FIG. Figure 6 As shown, the XRD test spectrum is as follows Figure 7 As shown; the prepared geopolymer recycled concrete (molded specimen) is as follows Figure 8 shown.

[0089] from Figure 6 and Figure 7 It can be seen that a large amount of gel phase is generated after the geopolymer reacts. Silicate ions, aluminate ions, and phosphate ions combine to form a three-dimensional network space structure, which corresponds to the diffraction peak in the XRD spectrum. The basic unit is -Si-O-Al-OPO-. The silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron generated by the reaction are interconnected to form a layered structure, which can effectively improve the mechanical properties of the geopolymer.

[0090] The waste polishing liquid acid-activated geopolymer regenerated concrete and the preparation method thereof of this embodiment have the following beneficial effects:

[0091] (1) Using waste red brick powder as a precursor and waste polishing liquid as an acid activator to prepare geopolymer mortar, and then obtaining geopolymer after high-temperature curing, the geopolymer has excellent mechanical properties. (2) The geopolymer can completely replace cement to prepare geopolymer concrete, and the geopolymer concrete has excellent road performance. (3) At the same time, waste materials such as waste red brick powder, waste polishing liquid, and high-brick-concrete construction waste recycled aggregate are comprehensively utilized to reduce carbon emissions.

[0092] Embodiment 2:

[0093] According to another preferred embodiment of the waste polishing liquid acid-activated geopolymer regenerated concrete and its preparation method of the present invention, its material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0094] The mass percentage of each substance in the geopolymer recycled concrete is 12wt% of geopolymer, 80wt% of aggregate, and 8wt% of water; the mass percentage of each substance in the geopolymer is 60wt% of waste red brick powder, 32wt% of waste polishing liquid, and 8wt% of deionized water.

[0095] The waste red brick powder is recycled powder obtained by processing construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 100%; the particle size distribution of the waste red brick powder is between 1-15μm, and the mass percentage of each particle size of the waste red brick powder is: 20wt% for particle size 8-15μm, and 80wt% for particle size 1-8μm.

[0096] In the waste red brick powder with a particle size of 8-15 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 45wt%, Al2O3 accounts for 30wt%, Fe2O3 accounts for 8wt%, CaO accounts for 5wt%, MgO accounts for 1wt%, Na2O accounts for 3wt%, K2O accounts for 3wt%, TiO2 accounts for 2wt%, P2O5 accounts for 2wt%, and MnO accounts for 1wt%.

[0097] In the waste red brick powder with a particle size of 1-8 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 60wt%, Al2O3 accounts for 20wt%, Fe2O3 accounts for 5wt%, CaO accounts for 5wt%, MgO accounts for 1wt%, Na2O accounts for 1wt%, K2O accounts for 3wt%, TiO2 accounts for 2wt%, P2O5 accounts for 2wt%, and MnO accounts for 1wt%.

[0098] The mass percentages of the chemical substances in the waste polishing liquid are as follows: 76wt% of phosphoric acid, 3wt% of sulfuric acid, 2wt% of nitric acid, 3wt% of Al ions, 5wt% of Fe ions, 2wt% of Ca ions, 1wt% of Mg ions, and 8wt% of water.

[0099] The mass percentage of each substance in the aggregate is: 24wt% of coarse aggregate, 36wt% of fine aggregate, and 40wt% of recycled aggregate from high-quality brick-concrete construction waste.

[0100] The coarse aggregate includes three particle sizes, and the mass percentage of each particle size in the coarse aggregate is: particle size 16-19mm accounts for 25wt%, particle size 9.5-16mm accounts for 42wt%, and particle size 4.75-9.5mm accounts for 33wt%. The coarse aggregate is limestone.

[0101] The fine aggregate includes seven particle sizes, and the mass percentage of each particle size in the fine aggregate is: particle size 2.36-4.75mm accounts for 22wt%, particle size 1.18-2.36mm accounts for 28wt%, particle size 0.6-1.18mm accounts for 20wt%, particle size 0.3-0.6mm accounts for 10wt%, particle size 0.15-0.3mm accounts for 5wt%, particle size 0.075-0.15mm accounts for 8wt%, and particle size 0-0.075mm accounts for 7wt%. The fine aggregate is limestone.

[0102] The high-grade brick-concrete construction waste recycled aggregate is a recycled aggregate obtained after processing of construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 70%; the high-grade brick-concrete construction waste recycled aggregate includes three particle sizes, and the mass percentage of each particle size of the high-grade brick-concrete construction waste recycled aggregate is: particle size 16-19mm accounts for 25wt%, particle size 9.5-16mm accounts for 45wt%, and particle size 4.75-9.5mm accounts for 30wt%.

[0103] In step 2, the main preparation parameters of the geopolymer include: placing the waste red brick powder with a particle size of 8-15 μm and the particle size of 1-8 μm in an oven for drying, the drying temperature is 80°C, and the drying time is 3 hours; adding the waste polishing liquid into deionized water for dilution to a phosphoric acid concentration of 8 mol / L; placing the waste red brick powder with a particle size of 8-15 μm and 30% of the acid activator in a mixing pot for mixing to form the first group of mortar, the mixing temperature is room temperature, the mixing speed is 80 r / min, and the mixing time is 1 50s; put the waste red brick powder with a particle size of 1-8μm and 70% of the acid activator into another mixing pot for mixing to form a second group of mortar, the mixing temperature is room temperature, the mixing speed is 80r / min, and the mixing time is 150s; put the first group of mortar and the second group of mortar into the same mixing pot for mixing, the mixing temperature is room temperature, the mixing speed is 150r / min, and the mixing time is 250s; put the molding mold and the molded parts inside it into the curing box for high temperature curing, the curing temperature is 60℃, and the curing time is 36h.

[0104] In step 3, the mixing temperature of geopolymer and water is room temperature, the mixing speed is 50r / min, and the mixing time is 120s.

[0105] In step 4, the drying temperature of coarse aggregate of each particle size, fine aggregate of each particle size, and high-grade brick-concrete construction waste recycled aggregate of each particle size is 80° C. and the drying time is 3 hours.

[0106] In step five, the mixing temperature of coarse aggregate of various particle sizes, fine aggregate of various particle sizes, high-brick-concrete construction waste recycled aggregate of various particle sizes, and fluid geopolymer is room temperature, the mixing speed is 150r / min, and the mixing time is 150s.

[0107] Embodiment three:

[0108] According to another preferred embodiment of the waste polishing liquid acid-activated geopolymer regenerated concrete and its preparation method of the present invention, its material ratio, process steps, technical principles, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0109] The mass percentage of each substance in the geopolymer recycled concrete is 20wt% of geopolymer, 72wt% of aggregate, and 8wt% of water; the mass percentage of each substance in the geopolymer is 68wt% of waste red brick powder, 25wt% of waste polishing liquid, and 7wt% of deionized water.

[0110] The waste red brick powder is recycled powder obtained by processing construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 100%; the particle size distribution of the waste red brick powder is between 1-15μm, and the mass percentage of each particle size of the waste red brick powder is as follows: the particle size of 8-15μm accounts for 40wt%, and the particle size of 1-8μm accounts for 60wt%.

[0111] In the waste red brick powder with a particle size of 8-15 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 50wt%, Al2O3 accounts for 25wt%, Fe2O3 accounts for 15wt%, CaO accounts for 2wt%, MgO accounts for 3wt%, Na2O accounts for 1wt%, K2O accounts for 1wt%, TiO2 accounts for 1wt%, P2O5 accounts for 1wt%, and MnO accounts for 1wt%.

[0112] In the waste red brick powder with a particle size of 1-8 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 65wt%, Al2O3 accounts for 15wt%, Fe2O3 accounts for 8wt%, CaO accounts for 2wt%, MgO accounts for 3wt%, Na2O accounts for 3wt%, K2O accounts for 1wt%, TiO2 accounts for 1wt%, P2O5 accounts for 1wt%, and MnO accounts for 1wt%.

[0113] The mass percentages of the chemical substances in the waste polishing liquid are as follows: 80wt% phosphoric acid, 3wt% sulfuric acid, 1wt% nitric acid, 4wt% Al ions, 2wt% Fe ions, 1wt% Ca ions, 1wt% Mg ions, and 8wt% water.

[0114] The mass percentage of each substance in the aggregate is 30wt% of coarse aggregate, 32wt% of fine aggregate, and 38wt% of recycled aggregate from high-quality brick-concrete construction waste.

[0115] The coarse aggregate includes three particle sizes, and the mass percentage of each particle size in the coarse aggregate is: particle size 16-19mm accounts for 35wt%, particle size 9.5-16mm accounts for 32wt%, and particle size 4.75-9.5mm accounts for 33wt%. The coarse aggregate is limestone.

[0116] The fine aggregate includes seven particle sizes, and the mass percentage of each particle size in the fine aggregate is: particle size 2.36-4.75mm accounts for 28wt%, particle size 1.18-2.36mm accounts for 22wt%, particle size 0.6-1.18mm accounts for 25wt%, particle size 0.3-0.6mm accounts for 7wt%, particle size 0.15-0.3mm accounts for 8wt%, particle size 0.075-0.15mm accounts for 5wt%, and particle size 0-0.075mm accounts for 5wt%. The fine aggregate is limestone.

[0117] The high-grade brick-concrete construction waste recycled aggregate is a recycled aggregate obtained after processing of construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 60%; the high-grade brick-concrete construction waste recycled aggregate includes three levels of particle size, and the mass percentage of each level of particle size in the high-grade brick-concrete construction waste recycled aggregate is: particle size 16-19mm accounts for 30wt%, particle size 9.5-16mm accounts for 38wt%, and particle size 4.75-9.5mm accounts for 32wt%.

[0118] In step 2, the main preparation parameters of the geopolymer include: placing the waste red brick powder with a particle size of 8-15 μm and the particle size of 1-8 μm in an oven for drying, the drying temperature is 100°C, and the drying time is 2 hours; adding the waste polishing liquid into deionized water for dilution to a phosphoric acid concentration of 12 mol / L; placing the waste red brick powder with a particle size of 8-15 μm and 50% of the acid activator in a mixing pot for mixing to form the first group of mortar, the mixing temperature is room temperature, the mixing speed is 120 r / min, and the mixing time is 100s; put the waste red brick powder with a particle size of 1-8μm and 50% of the acid activator into another mixing pot for mixing to form a second group of mortar, the mixing temperature is room temperature, the mixing speed is 120r / min, and the mixing time is 100s; put the first group of mortar and the second group of mortar into the same mixing pot for mixing, the mixing temperature is room temperature, the mixing speed is 200r / min, and the mixing time is 200s; put the molding mold and the molded parts inside it into the curing box for high temperature curing, the curing temperature is 80℃, and the curing time is 24h.

[0119] In step 3, the mixing temperature of geopolymer and water is room temperature, the mixing speed is 80r / min, and the mixing time is 90s.

[0120] In step 4, the drying temperature of coarse aggregate of each particle size, fine aggregate of each particle size, and high-grade brick-concrete construction waste recycled aggregate of each particle size is 100° C. and the drying time is 2 h.

[0121] In step five, the mixing temperature of coarse aggregate of various particle sizes, fine aggregate of various particle sizes, high brick-concrete construction waste recycled aggregate of various particle sizes, and fluid geopolymer is room temperature, the mixing speed is 200r / min, and the mixing time is 120s.

[0122] The geopolymers prepared in the above three embodiments were subjected to mechanical property tests and water absorption tests. Each test must comply with the corresponding test operation specifications, such as the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). The test results are shown in Table 1. Similarly, the geopolymer mixed recycled concrete prepared in the above three embodiments was subjected to mechanical property tests and durability tests. Each test must comply with the corresponding test operation specifications, such as the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). The test results are shown in Table 2. The test equipment, test environment, test conditions, sample shape and size used in each test were the same.

[0123] Table 1 Mechanical properties and water absorption test results of geopolymers

[0124]

[0125] Table 2 Mechanical properties and durability test results of geopolymer recycled concrete

[0126]

[0127] It can be seen from the test results in Table 1 and Table 2 that the geopolymers prepared in the above three embodiments have excellent mechanical properties and water absorption, and the prepared geopolymer recycled concrete has good mechanical properties and durability.

[0128] The coarse aggregate and fine aggregate used in the above embodiments were purchased from Beijing Municipal Road and Bridge Building Materials Group Co., Ltd.; the brick-concrete construction waste recycled aggregate used was purchased from Beijing Urban Green Source Environmental Protection Technology Co., Ltd., mainly from construction waste generated by the demolition of brick-concrete buildings within 30 kilometers of the disposal site; the waste polishing liquid used was purchased from Beijing Tianhai Nanjiao Electroplating Factory.

[0129] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0130] It is not difficult for those skilled in the art to understand that the waste polishing liquid acid-activated geopolymer regenerated concrete and its preparation method of the present invention include any combination of the invention content and specific implementation methods of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A waste polishing liquid acid-activated geopolymer regeneration concrete, characterized by: The mass percentage of each substance in the geopolymer recycled concrete is 12-20wt% of geopolymer, 72-80wt% of aggregate, 8-10wt% of water, and the sum of the contents of each substance is 100wt%; the mass percentage of each substance in the geopolymer is 60-68wt% of waste red brick powder, 25-32wt% of waste polishing liquid, and 7-12wt% of deionized water, and the sum of the contents of each substance is 100wt%.

2. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 1, characterized in that: The waste red brick powder is recycled powder obtained by processing construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 100%; the particle size distribution of the waste red brick powder is between 1-15μm, and the mass percentage of each particle size of the waste red brick powder is as follows: the particle size of 8-15μm accounts for 20-40wt%, and the particle size of 1-8μm accounts for 60-80wt%.

3. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 2, characterized in that: In the waste red brick powder with a particle size of 8-15 μm, the mass percentage of each chemical substance in the waste red brick powder is: SiO2 accounts for 45-50wt%, Al2O3 accounts for 25-30wt%, Fe2O3 accounts for 8-15wt%, CaO accounts for 2-5wt%, MgO accounts for 1-3wt%, Na2O accounts for 1-3wt%, K2O accounts for 1-3wt%, TiO2 accounts for 1-2wt%, P2O5 accounts for 1-2wt%, MnO accounts for 0.5-1wt%, and the sum of the contents of each chemical substance is 100wt%.

4. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 3, characterized in that: In the waste red brick powder with a particle size of 1-8 μm, the mass percentage of each chemical substance in the waste red brick powder is 60-65wt% of SiO2, 15-20wt% of Al2O3, 5-8wt% of Fe2O3, 2-5wt% of CaO, 1-3wt% of MgO, 1-3wt% of Na2O, 1-3wt% of K2O, 1-2wt% of TiO2, 1-2wt% of P2O5, and 0.5-1wt% of MnO, and the sum of the contents of each chemical substance is 100wt%.

5. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 4, characterized in that: The mass percentages of the chemical substances in the waste polishing liquid are as follows: phosphoric acid 76-80wt%, sulfuric acid 3-5wt%, nitric acid 1-2wt%, Al ions 3-8wt%, Fe ions 2-5wt%, Ca ions 1-2wt%, Mg ions 1-2wt%, water 8-11wt%, and the sum of the contents of the chemical substances is 100wt%.

6. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 5, characterized in that: The mass percentage of each substance in the aggregate is 24-30wt% of coarse aggregate, 32-38wt% of fine aggregate, and 35-40wt% of recycled aggregate from high-quality brick-concrete construction waste. The sum of the contents of each substance is 100wt%.

7. The waste polishing liquid acid-activated geopolymer regeneration concrete according to claim 6, characterized in that: The coarse aggregate includes three particle sizes, and the mass percentage of each particle size in the coarse aggregate is 25-35wt% for a particle size of 16-19mm, 32-42wt% for a particle size of 9.5-16mm, and 30-40wt% for a particle size of 4.75-9.5mm. The sum of the contents of the coarse aggregates of each particle size is 100wt%. The coarse aggregate includes any one or more of limestone, basalt, and granite. The fine aggregate comprises seven particle sizes, and the mass percentage of each particle size in the fine aggregate is as follows: particle size 2.36-4.75 mm accounts for 22-28 wt%, particle size 1.18-2.36 mm accounts for 22-28 wt%, particle size 0.6-1.18 mm accounts for 20-25 wt%, particle size 0.3-0.6 mm accounts for 7-10 wt%, particle size 0.15-0.3 mm accounts for 5-8 wt%, particle size 0.075-0.15 mm accounts for 5-8 wt%, particle size 0-0.075 mm accounts for 5-8 wt%, and the sum of the content of fine aggregates of each particle size is 100 wt%; the fine aggregate comprises any one or more of limestone, basalt, and granite; The high-grade brick-concrete construction waste recycled aggregate is a recycled aggregate obtained after processing of construction waste generated by the demolition of brick-concrete buildings, and its brick-concrete content is 60-70%; the high-grade brick-concrete construction waste recycled aggregate includes three particle sizes, and the mass percentage of each particle size in the high-grade brick-concrete construction waste recycled aggregate is: particle size 16-19mm accounts for 25-30wt%, particle size 9.5-16mm accounts for 38-45wt%, and particle size 4.75-9.5mm accounts for 30-35wt%, and the sum of the content of each particle size high-grade brick-concrete construction waste recycled aggregate is 100wt%.

8. A method for preparing acid-activated geopolymer regenerated concrete from waste polishing liquid, characterized in that: The method for preparing the waste polishing liquid acid-activated geopolymer regenerated concrete according to any one of claims 1 to 7 comprises the following steps in order: Step 1: Weigh all raw materials according to the designed material ratio; Step 2: Prepare geopolymer according to the designed material ratio and process parameters; Step 3: Put the geopolymer and water into a mixing pot and mix them to make the geopolymer completely dispersed to form a fluid geopolymer; Step 4: Put the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the recycled aggregates of high-quality brick-concrete construction waste of various particle sizes into an oven for drying; Step 5: After the drying process is completed, the coarse aggregates of various particle sizes, the fine aggregates of various particle sizes, and the high-brick-concrete construction waste recycled aggregates of various particle sizes are put into the mixing pot and mixed with the fluid geopolymer to obtain the waste polishing liquid acid-activated geopolymer recycled concrete.

9. The method for preparing acid-activated geopolymer regenerated concrete using waste polishing liquid according to claim 8, characterized in that: In step 2, the method for preparing the geopolymer comprises the following steps in order: Step (1): crushing, grinding and screening construction waste generated by demolishing brick-concrete buildings with a brick-concrete content of 100% to obtain waste red brick powder; Step (2): weighing waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm according to the designed material ratio, and putting them into an oven for drying respectively, the drying temperature is 80-100° C., and the drying time is 2-3 h; after the drying treatment is completed, taking out the waste red brick powder with a particle size of 8-15 μm and a particle size of 1-8 μm from the oven respectively, and cooling them naturally to room temperature; Step (3): According to the designed chemical content ratio, the chemical substances in the waste red brick micropowder with a particle size of 8-15 μm and a particle size of 1-8 μm are tested respectively to ensure that the content of each chemical substance in the waste red brick micropowder of each particle size meets the design requirements; Step (4): according to the designed material ratio, the waste polishing liquid is added into deionized water for dilution to a phosphoric acid concentration of 8-12 mol / L, sealed and naturally cooled to room temperature to obtain an acid activator; Step (5): putting waste red brick powder with a particle size of 8-15 μm and part of the acid activator into a mixing pot for mixing to form a first group of mortar, wherein the mass of the part of the acid activator is 30-50% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 80-120 r / min, and the mixing time is 100-150 s; Step (6): putting the waste red brick powder with a particle size of 1-8 μm and the remaining acid activator into another mixing pot for mixing to form a second group of mortar, wherein the mass of the remaining acid activator is 50-70% of the total amount of the acid activator, the mixing temperature is room temperature, the mixing speed is 80-120 r / min, and the mixing time is 100-150 s; Step (7): putting the first group of mortar and the second group of mortar into the same mixing pot for mixing, the mixing temperature is room temperature, the mixing speed is 150-200r / min, and the mixing time is 200-250s to obtain geopolymer mortar, which is in a fluid state; Step (8): filling the geopolymer mortar into the molding mold, and using a scraper to scrape the upper surface of the geopolymer mortar in the molding mold flat; placing the molding mold filled with the geopolymer mortar on an electric vibration table, starting the electric vibration table, and starting vibration molding. During the vibration molding process, if a depression occurs, the geopolymer mortar is added to the depressed part; Step (9): After the vibration molding is completed, the molding mold and the molded part inside are placed in a curing box for high-temperature curing, the curing temperature is 60-80° C., and the curing time is 24-36 hours; after the high-temperature curing is completed, demoulding is performed, and then the molded part is subjected to standard curing under sealed conditions, the curing temperature is room temperature, and the curing time is 28 days, so that the geopolymer is obtained, and the geopolymer is in a solid state.

10. The method for preparing acid-activated geopolymer regenerated concrete from waste polishing liquid according to claim 9, characterized in that: In step 3, the mixing temperature of geopolymer and water is room temperature, the mixing speed is 50-80r / min, and the mixing time is 90-120s; In step 4, the drying temperature of the coarse aggregate of each particle size, the fine aggregate of each particle size, and the high brick-concrete construction waste recycled aggregate of each particle size is 80-100° C. and the drying time is 2-3 hours; In step five, the mixing temperature of coarse aggregate of various particle sizes, fine aggregate of various particle sizes, high brick-concrete construction waste recycled aggregate of various particle sizes, and fluid geopolymer is room temperature, the mixing speed is 150-200r / min, and the mixing time is 120-150s.

Citation Information

Patent Citations

  • Synthetic method of geopolymer

    CN103864322A

  • Alkali-activated recycled red brick micro-powder synergistic slag-based recycled concrete and preparation method thereof

    CN112479674A

  • Stone for acid-activated multi-element waste ecological gabion and preparation method thereof

    CN116768537A

  • Acid-excited geopolymer and preparation method thereof

    CN118812194A